Designing a professional development program for mathematics teachers for effective use of technology in teaching - Getenet, Seyum Tekeher (Education and information technologies, 2020)
The present study demonstrated the importance and procedures of learners and learning context analysis to design a context-driven professional development program to effectively use of technology in mathematics classrooms. The study was conducted at departments of mathematics in two Colleges of Teacher Education using a combination of qualitative and quantitative data. The data were collected from 16 mathematics teacher educators through a questionnaire, interviews, classroom observations and focus group discussions. The data were analysed using descriptive statistics of quantitative data and theme grouping of the qualitative data. The study showed that analyses of the learning context and teacher educators’ context were essential to design a context-driven professional development program containing relevant examples, contents, and scenarios for teachers. The findings of this study can provide a more practical approach and a model that could be adopted for studies aimed at designing a context-driven professional development program and influencing practices.